REDISCOVERING THE SCIENTIFIC AND DIDACTIC VALUE OF MINOR HERBARIUM COLLECTIONS: THE SEEDS AND FRUITS COLLECTION BY GUSTAVO BONAVENTURA - Abbate, G.; Latini, M.; Giovi, E.; Mussino, F.; Pierfranceschi, M.; Millozza, A. (Annali di Botanica, 2018)
Seeds and fruits collections are very important from a systematic point of view and represent useful references in several disciplines and research fields. The Herbarium of Sapienza University of Rome (RO) hosts a Spermoteque/Carpoteque, which was organized by Gustavo Bonaventura (1902–1976). The purpose of this paper is to describe the heritage of Bonaventura's collection. It consists of 42 wooden boxes, globally hosting 3411 glass tubes containing seeds, fruits, and other materials. The collection was first of all catalogued; then, analysis were conducted regarding taxonomic composition, temporal and geographic coverage, institutions of provenience, collectors, content, and preservation status. The specimens refer to 2740 taxa, belonging to 890 genera and 135 families. Many genera of agricultural interest are present, each one with different cultivars. The collection spans across 130 years (1843–1975) and hosts specimens coming from all over the world. Materials were provided by several herbaria, botanical gardens and agrarian institutes, and by 50 collectors. The Bonaventura’s collection is still a useful reference collection, testifying biodiversity over times and thus being useful for diachronic studies; moreover, it documents the interests of collectors and the past network activity between institutions.